Deposition and Characterisation of Pd-xSb2S3 Thin Films for Sustainable Solar Energy Applications - Nwofe, Patrick; Idenyi, Ndubisi Edennaya (UI Scholars Hub, 2017)
This study reports on the effects of different concentrations of palladium impurities on the optical and compositional properties of palladium-doped antimony sulfide (Pd-xSb2S3) thin films grown by the chemical bath deposition method. The films were grown at room temperature (25 °C) with other condition, such as pH at 3.2 and the complexing agent (polyvinyl alcohol), was kept constant. The concentration of the dopants was varied between 0.3 and 0.5 M. The films were annealed at an annealing temperature of 100 °C with the annealing time of 90 min. The films were characterized using the Rutherford backscattering spectrometry (RBS) techniques and optical spectroscopy (transmittance versus wavelength and absorbance versus wavelength) to investigate the composition and optical constants (optical absorption coefficient, energy bandgap, and extinction coefficient), respectively. The results show that the transmittances of the doped layers were higher than that of the as-deposited layers. The energy bandgap of the layers was direct and typically ≤ 2.80 eV.